Clinical efficacy and safety evaluation of a novel fractional unipolar radiofrequency device on facial tightening: A preliminary report. (13th February 2017) - Suh, Dong Hye; Byun, Eun Jung; Lee, Sang Jun; Song, Kye Yong; Kim, Hei Sung
Summary: Background: Previous studies have shown that radiofrequency (RF) energy is safe and effective for improving skin laxity. Unlike monopolar and bipolar devices, little has been studied with the unipolar hand piece. Objectives: We sought to evaluate the safety and efficacy of a novel fractional unipolar RF device on facial tightening. Patients and Methods: This was a retrospective, single‐center study of 14 subjects with age‐related facial laxity who underwent five sessions of fractional unipolar RF at an interval of 2 weeks, and then followed‐up for 3 months. Standardized photos were taken at baseline and at 3‐months follow‐up, and were assessed by two independent dermatologists using a 4‐point scale (0=no improvement, 1=mild improvement, 2=moderate improvement, 3=significant improvement). Punch biopsies (2 mm) were performed and a questionnaire was used to evaluate the patient's satisfaction and the incidence of adverse reactions. Results: Fourteen subjects with mild to moderate age‐related facial laxity were included in the study. The mean age of the subjects was 49.7 years (range 32‐80). 35.7% of the subjects showed significant improvement, 50% moderate improvement, and 14.3% slight improvement of facial laxity in their follow‐up photos. About 85.7% of the patients replied that they were either greatly satisfied or satisfied with the results at 3‐months follow‐up. Skin biopsies revealed an increase in collagen in the dermis. None of the subjects experienced any serious adverse events during or after the procedure. Conclusion: Our findings suggest that fractional Unipolar RF can be safely performed on the face and is effective in skin tightening. It has a great advantage over other forms of RF by being entirely painless.